2018
DOI: 10.1089/ast.2017.1737
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanet Biosignatures: A Framework for Their Assessment

Abstract: Finding life on exoplanets from telescopic observations is an ultimate goal of exoplanet science. Life produces gases and other substances, such as pigments, which can have distinct spectral or photometric signatures. Whether or not life is found with future data must be expressed with probabilities, requiring a framework of biosignature assessment. We present a framework in which we advocate using biogeochemical “Exo-Earth System” models to simulate potential biosignatures in spectra or photometry. Given actu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
195
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(201 citation statements)
references
References 280 publications
(345 reference statements)
3
195
0
3
Order By: Relevance
“…E-ELT). However, whether or not the detected chemical will be a robust signature of life is a subject of much debate (179,49). Nevertheless, the prospects of finding a potential biosignature in the atmosphere of a terrestrial exoplanet are promising given the rapid increase in new discoveries of such planets and the new observational facilities on the horizon.…”
Section: Habitable Planets and Biosignaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…E-ELT). However, whether or not the detected chemical will be a robust signature of life is a subject of much debate (179,49). Nevertheless, the prospects of finding a potential biosignature in the atmosphere of a terrestrial exoplanet are promising given the rapid increase in new discoveries of such planets and the new observational facilities on the horizon.…”
Section: Habitable Planets and Biosignaturesmentioning
confidence: 99%
“…Nevertheless, the prospects of finding a potential biosignature in the atmosphere of a terrestrial exoplanet are promising given the rapid increase in new discoveries of such planets and the new observational facilities on the horizon. Recent reviews of various aspects of this area can be found in (179,49,87,228,163)…”
Section: Habitable Planets and Biosignaturesmentioning
confidence: 99%
“…However, far fewer investigations have been conducted as to the favorability of M-dwarf planets for abiogenesis (the origin of life), i.e., whether life as we know it could emerge on these worlds. Investigations of the ease with which life can originate on different worlds are relevant to prioritization of targets for biosignature search, and for interpretation of putative biosignatures detected from such objects (e.g., Catling et al 2017). In part, the paucity of work on this question is due to limitations in our understanding of the origin of life.…”
Section: Introductionmentioning
confidence: 99%
“…The prebiotic disequilibrium anti-biosignature is, in principle, remotely detectable on exoplanets. Strong spectral signatures of atmospheric CO2, CO and H2O exist, and could be detected with reflectance or transmission spectroscopy (Catling et al 2018). The presence of prebiotic H2 could be inferred with its spectral feature at , or its continuous features in the near-infrared and < .…”
Section: Detecting the Prebiotic Earth Disequilibrium Anti-biosignaturementioning
confidence: 99%